A comparative analysis of carcass and meat traits, and rumen bacteria between Chinese Mongolian sheep and Dorper × Chinese Mongolian crossbred sheep - Jinzhu Xiang; Liang Zhong; Hui Luo; Lingbo Meng; Yanbing Dong; Zhi Qi; Hanning Wang (Animal, 2022)
Mutton is one of the most widely consumed meats globally. The Chinese Mongolian sheep (MS) breed is an indigenous breed of sheep characterised by high-quality meat and strong adaptability. Dorper × Chinese Mongolian crossbred sheep (DS) is an improved breed with a rapid growth rate and high mutton yield found in parts of China. The rumen microbiota is known to play a key role in shaping host nutrition and health. However, the carcass traits and meat nutritional qualities of DS and MS remain poorly defined, as does how rumen microbes affect these characteristics. The objective of this study was to compare carcass profiles, rumen bacterial communities, and meat nutritional qualities between MS and DS and clarify the associations between rumen microbiota and meat nutritional composition. We found that DS had a faster growth rate and better carcass traits than MS, including BW, carcass weight, meat weight, and loin-eye area. We further found that metabolite and rumen bacterial community composition differed between the two sheep breeds. First, compared with MS, DS had lower contents of some sweet amino acids, monounsaturated fatty acids, n-3 polyunsaturated fatty acids, and beneficial metabolites. Secondly, MS and DS had distinct rumen bacterial compositions, and these differential bacteria were related to carcass traits as well as to contents of meat amino acids, free fatty acids, and other metabolites. Taken together, our data showed that DS had better carcass characteristics but lower meat nutritional quality, parameters that were associated with differences in rumen bacterial community composition. These findings may benefit future breeding strategies aimed at improving sheep carcass performance and meat quality worldwide.